2010
DOI: 10.1136/bjo.2009.166314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retinal nerve fibre layer thickness measurements calculated by the optic nerve head map (NHM4) and RNFL3.45 modes of spectral-domain optical coherence tomography (RTVue-100)

Abstract: RNFL thickness determined by direct scanning and re-sampling from datasets of RTVue-100 OCT were in good agreement. However, both measurements in glaucomatous subjects were significantly different from those with the Stratus OCT. Those findings should be considered when a patient is followed-up using different types of OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Indeed, retinal nerve fiber layer (RNFL) thickness is a key diagnostic feature for glaucoma, multiple sclerosis, and optic neuropathies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Quantitative RNFL thickness measurement has become possible with the development of imaging technologies, such as optical coherence tomography (OCT). Recently, the introduction of spectral-domain OCT (SD-OCT) has greatly enhanced the image resolution, decreasing the scan acquisition time, and has also improved measurement reproducibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, retinal nerve fiber layer (RNFL) thickness is a key diagnostic feature for glaucoma, multiple sclerosis, and optic neuropathies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Quantitative RNFL thickness measurement has become possible with the development of imaging technologies, such as optical coherence tomography (OCT). Recently, the introduction of spectral-domain OCT (SD-OCT) has greatly enhanced the image resolution, decreasing the scan acquisition time, and has also improved measurement reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…5,6,8,[11][12][13][14][15][16][17][18][19][20][21][22][23] The present investigation was designed to appraise for the first time in literature the agreement among seven commercially available OCT devices, and to evaluate intra-and interoperator reproducibility in assessment of average peripapillary RNFL thickness and four-quadrant values in healthy subjects without ocular pathologies. For a comprehensive approach, we enhanced the statistical analysis by further investigations on device disagreement in terms of systematic bias and random error, using a structural equation model.…”
Section: Resultsmentioning
confidence: 99%
“…All of inter-visit, and intra-and inter-operator variation might be in play. However, our previous work on reproducibility of cRNFL thickness measurements, using the same device, showed that cRNFL measurements were highly reproducible from visit to visit [30]. Also, good intra-and inter-session reproducibility of cRNFL and mGCC measurements on both healthy and glaucomatous eyes has been reported [31,32].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the variations in the optic disc centering during scanning could be a potential limitation of our study, which used the RNFL 3.45 protocol; nevertheless, all of the images in the current study were acquired by the same experienced technician to minimize optic disc decentering and to avoid interoperator variability. In addition, Shin et al [31] demonstrated that the measurement reproducibilities of these 2 RTVue protocols were excellent, and that the RNFL thicknesses measured by both protocols were in good agreement.…”
Section: Discussionmentioning
confidence: 99%